ENT 530 Social Media Portfolio: PrettyGang.Co / Farah Hanis Fauzi - Fauzi, Farah Hanis (2021)
This report is about pitching about the business that I have chosen which is PrettyGang. Co. PrettyGang. Co is a fashion line business that sells good quality t-shirts, crop top and baby rompers that is spreads awareness on the beauty of Black Asian community in Malaysia. The owner of the business is Husna Aiza binti Rahman a 26-year-old woman who started the business in 2017.